2014
DOI: 10.1590/0034-737x201461060011
|View full text |Cite
|
Sign up to set email alerts
|

Alteração do crescimento e dos teores de nutrientes com utilização de fertilizante organomineral em cenoura

Abstract: Change in growth and nutrient content in carrots with the use of biofertilizerThe use of organo-mineral biofertilizers containing alga extracts is recent in Brazil. Thus, the objective of this study was to evaluate the effect of leaf application of Ascophyllum nodosum extract biofertilizer (Activo®) on growth and on the nutrient content of carrot. The experiment was carried out in the garden area at Paraná Federal University, in the city of Pinhais, State of Paraná, in 2009, in an organic system, using the cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 8 publications
1
4
0
1
Order By: Relevance
“…Studies conducted by Bruno et al (2007) and Oliveira et al (2007b) concluded that organo-mineral fertilizers improve crop productivity and plant morphological parameters such as length and diameter of roots, and improve the uptake of nutrients by roots (PEDROSA et al, 2007). Kaseker et al (2014) evaluating the effects of organomineral fertilizers on carrot, also noted increased accumulation of nutrients in plants, even in a highly fertile soil -conditions similar to this studyemphasizing, therefore, better efficiency of organomineral fertilizers. Figure 1 (A, B, C, D and E) shows accumulation curves of micronutrient (Cu, Fe, Mn and Zn, respectively) in potato leaves, stems and tubers during crop cycle in the organo-mineral treatment.…”
Section: Resultssupporting
confidence: 82%
“…Studies conducted by Bruno et al (2007) and Oliveira et al (2007b) concluded that organo-mineral fertilizers improve crop productivity and plant morphological parameters such as length and diameter of roots, and improve the uptake of nutrients by roots (PEDROSA et al, 2007). Kaseker et al (2014) evaluating the effects of organomineral fertilizers on carrot, also noted increased accumulation of nutrients in plants, even in a highly fertile soil -conditions similar to this studyemphasizing, therefore, better efficiency of organomineral fertilizers. Figure 1 (A, B, C, D and E) shows accumulation curves of micronutrient (Cu, Fe, Mn and Zn, respectively) in potato leaves, stems and tubers during crop cycle in the organo-mineral treatment.…”
Section: Resultssupporting
confidence: 82%
“…The average population size at harvest was 294,000 plants per hectare, within the recommended range for the M6410 IPRO cultivar. Although the biostimulant studied here contains auxins (STIRK et al, 2004) and can therefore potentially affect plant height (TAIZ et al, 2017), and other authors have reported an increase in this variable with the application of seaweed extracts in different crops (SILVA et al, 2010;KASEKER et al, 2014;BACKES et al, 2017), this effect was not independent of biostimulant dose and application time (Figure 2, B1 and B2). However, the aforementioned authors studied the effects of Ascophyllum nodosum application, whereas the present study used a biostimulant made from Ecklonia maxima extract.…”
Section: Resultsmentioning
confidence: 60%
“…These authors observed a high frequency of splits in the roots of radishes cultivated using earthworm humus and bovine manure. Kaseker et al (2014) also concluded that the application of organic fertilizers (bovine manure) may contribute to an increase in the malformation of carrot roots. Bregonci et al (2008) found that the oscillations in the water content and temperature of the soil, in particular its surface layer, resulting from high temperatures and the lack of mulch, which favors rapid evapotranspiration, contribute directly to the splitting of tuberous roots.…”
Section: Resultsmentioning
confidence: 99%